2016
DOI: 10.3390/molecules21101365
|View full text |Cite
|
Sign up to set email alerts
|

The Electroluminescence Mechanism of Solution-Processed TADF Emitter 4CzIPN Doped OLEDs Investigated by Transient Measurements

Abstract: High efficiency, solution-processed, organic light emitting devices (OLEDs), using a thermallyactivated delayed fluorescent (TADF) emitter, 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN), are fabricated, and the transient electroluminescence (EL) decay of the device with a structure of [ITO/PEDOT: PSS/4CzIPN 5 wt % doped 4,40-N,N0-dicarbazolylbiphenyl(CBP)/bis-4,6-(3,5-di-4-pyridylphenyl)-2-methylpyrimidine (B4PyMPM)/lithium fluoride (LiF)/Al], is systematically studied. The results shed light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The phenomena are related to the emissive layer only and are consistent with the emission red shifts reported in solution-processed and evaporated films by others. 9,10,1216 Device data shown in Figure 6c,d demonstrate that the monomer and dimer concentrations within the emissive layer play a dominant role in all aspects of the device performance, both electrical and optical. The current–voltage ( J – V ) and EQE curves for the full device series are shown in Figure S18.…”
Section: Resultsmentioning
confidence: 98%
“…The phenomena are related to the emissive layer only and are consistent with the emission red shifts reported in solution-processed and evaporated films by others. 9,10,1216 Device data shown in Figure 6c,d demonstrate that the monomer and dimer concentrations within the emissive layer play a dominant role in all aspects of the device performance, both electrical and optical. The current–voltage ( J – V ) and EQE curves for the full device series are shown in Figure S18.…”
Section: Resultsmentioning
confidence: 98%
“…1. 98 Wang et al 99 reported 4CzIPN ( Fig. 1) and utilized this material to provide evidence that the mechanism of electroluminescence of devices based on 4CzIPN is based on the recombination of injected carriers in the (near) absence of energy transfer processes.…”
Section: Carbazole-based Materials As Tadf Emittersmentioning
confidence: 99%
“…They observed a significant redshift in the emission with increasing concentration (Figures 2A-E) and a decrease in the TADF lifetime. These red shifts, both in photoluminescence and electroluminescence, have been observed by a range of researchers (Nakanotani et al, 2013;Kim and Lee, 2014;Komatsu et al, 2015;Wang et al, 2016;Zhu et al, 2017;Li et al, 2018;Niwa et al, 2018). Kim et al (2017) attributed these red shifts and the consequential change in TADF behavior to the changing dipole moment of the surrounding matrix as the host molecules are subsequently replaced with more 4CzIPN molecules (Figure 2A).…”
Section: Uncovering Intermolecular Effects In Existing Motifsmentioning
confidence: 75%